DESIGNING DIGITAL BUSINESS MODELS FOR GEN Z: A CUSTOMER-CENTRIC APPROACH TO ENGAGEMENT - Ramli, Norliza (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
As the digital economy accelerates, Malaysian SMEs in the food and beverage (F&B) sector must adopt customer-centric digital strategies to remain competitive. Despite increased digital adoption, many SMEs still fall short in aligning digital initiatives with customer engagement, limiting their impact on long-term performance. This study investigates how four digital transformation enablers digital literacy and usage behavior, digital service convenience, product innovation and customization, and interface and communication experience influence customer engagement among Gen Z consumers engaging with F&B SMEs in Malaysia. Data were collected from 300 respondents with prior digital interactions with F&B SMEs. Reliability analysis using Cronbach’s Alpha confirmed high internal consistency across all constructs (α = 0.80–0.85). Multiple Linear Regression was applied to assess the strength and significance of each relationship. All four predictors showed significant positive effects on customer engagement (p < 0.001), with digital literacy and interface and communication experience identified as the strongest contributors. The findings underscore the importance for SMEs to move beyond basic digital presence by offering seamless, personalized, and innovation-driven digital experiences. To deepen customer engagement and remain relevant in a competitive digital marketplace, F&B SMEs must prioritize investment in user-centric design, responsive digital communication, and tailored product offerings that reflect evolving customer expectations.